Low-latitude Pi2 oscillations observed by polar Low Earth Orbiting satellite - Thomas, Neethal; Vichare, Geeta; Sinha, Ashwini K.; Rawat, Rahul (JGR, 120, p. 7838–7856, doi:10.1002/ 2014JA020958, 2015)
Low-latitude Pi2 pulsations in the topside ionosphere are investigated using vector magnetic field measurements from LEO satellite, CHAMP, and underneath ground station. Substorm-associated Pi2s are initially identified using high-resolution data from Indian station Shillong, during 2007–2009, and are further classified into three subgroups of Pi2 band (6–25 mHz), based on its frequency. During nighttime, coherent in-phase oscillations are observed in the compressional component at satellite and horizontal component at underneath ground station for all the Pi2 events, irrespective of the Pi2 frequency. We observe that the identification of daytime Pi2s at CHAMP (compressional component) depends on the frequency of Pi2 oscillation; i.e., 40%, 45%, and 100% of Pi2 events observed in dayside ground station with frequency between 6–10 mHz, 10–15 mHz, and 15–25 mHz were identified at satellite, respectively. At CHAMP during daytime, the presence of a dominant power in the lower frequencies of Pi2 band, which is unique to satellite, is consistently observed and can modify the Pi2 oscillations. Pi2s having frequency >15 mHz are less affected by these background frequencies, and a clear signature of daytime Pi2s at CHAMP is possible to observe, provided that contribution from non-Pi2 frequencies at satellite from the lower end of Pi2 band is eliminated. Daytime Pi2s identified in the topside ionosphere showed coherent but mostly opposite phase oscillations with underneath ground station, and satellite-to-ground amplitude ratio is, in general, found to be less than 1. Present results indicate that a combination of fast cavity-mode oscillations and an instantaneous transmission of Pi2 electric field from high- to low-latitude ionosphere is responsible for the observation of daytime Pi2s.
Keywords: Pi2 pulsations; Low earth orbiting satellite; Ionosphere